ISSUES OF SCREENING IN THE SOCIALLY RESPONSIBLE INVESTMENT MARKET: THE CURRENT STATE OF SUPPLY-DEMAND RELATIONSHIP AND FINANCIAL IMPACT - TRAN, DUY HUNG (2013)
Although the screening strategy plays the key role in the development of the SRI market, little effort has been spent on researching the features of the screening product. This paper is conducted in an attempt to fill the gap in the academia. Two focuses of this paper are (1) studying the gap between supply and demand sides in the market for SRI screening and (2) examining the effect of SRI screening to financial performance. For the first focus, it is found that SRI suppliers and investors disagree in giving the SRI screening’s mission and in deciding the number of screens adopted in the screening process; as well as there are problems in the transparency of funds’ screening. For the second focus, there is evidence of effect of screening approaches, and no effect of the number of screens and of the type of screens to funds’ financial performance. Those findings are hoped to contribute to build a more stable growth of the SRI market.